PENGARUH DISIPLIN DAN PARTISIPASI SISWA TERHADAP PRESTASI BELAJAR MELAKSANAKAN KOMUNIKASI BISNIS SISWA SMK DI KECAMATAN DAWARBLANDONG DENGAN PERCAYA DIRI SEBAGAI VARIABEL MODERASI - Cahya, Septyan Budy (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to analyze the influence of the discipline of learning and participation on student achievement with confidence as moderation. The population is class X in academic year 2013-2014 with a total of 117 students. 88 students Samples were taken by using simple random sampling technique. Research using method of explanation by quantitative approach that consists of learning the discipline, participation, confidence, and learning achievement. The results showed the discipline of learning and participation has a positive influence and significant on student achievement both partially and simultaneously. Confidence no significant effect as a moderating influence on the learning achievement of learning discipline. Confidence has significant effect as a moderation influencing student participation on learning achievement. Simultaneously there is a positive and significant impact on the discipline of learning and participation influences on student achievement in class X SMK the district of Dawarblandong